Pengaruh Kepemimpinan Transformasional Dan Motivasi Terhadap Kinerja Pegawai: (Studi pada salah satu pemerintahan daerah di Kota Bandung) - Habibah Syahidah; Adhie Fasha Nurhadian; Ujang Wawan Sam Adinata; Asep Rochyadi Suherman (Center of Research, STIE Pasundan, Bandung, Indonesia., 2021)
Good employee performance is one of the goals of the organization in order to produce superior performance. This study aimed to determine the effect of transformational leadership and motivation on employee performance. The research method used is quantitative research methods with path analysis techniques using a sample of 97 employees at one of the local government agencies in Bandung. The results showed a significant influence of transformational leadership and motivation on employee performance. The results of the study recommend that agencies make efforts to increase leadership and motivation to produce superior performance.